Lymphaticovenular anastomosis in the treatment of secondary lymphoedema of the legs after cancer treatment. Issue 7 (July 2019) - Phillips, Georgina S.A.; Gore, Sinclair; Ramsden, Alex; Furniss, Dominic
Summary: Objective: As survival from cancer continues to improve, greater importance is placed on quality of life after surgery. Lymphoedema is a common and disabling complication of cancer treatment. Lymphaticovenular anastomosis (LVA) is a supermicrosurgical treatment option for lower limb lymphoedema. The aim of this study was to assess the effectiveness of LVA in reducing limb volume and its effect on quality of life of patients with secondary leg lymphoedema following treatment for cancer, including gynaecological cancers. Methods: Limb volume and patient rated quality of life were collected prospectively pre-operatively and at every post-operative appointment in this case series. All patients presenting to the clinic with stable or progressive leg lymphoedema despite conservative therapy who were suitable candidates for LVA over a three-year period were included. Results: Twenty-nine patients were treated with LVA, 19 for unilateral lymphoedema and 10 for bilateral. In unilateral cases median limb excess volume reduced from 27% to 16% post-operatively ( p < 0.005) and in bilateral cases a median 8% reduction in absolute limb volume was achieved. Significant improvement in patient-reported quality of life was demonstrated, as measured by the LYMQOL: 23% improvement in unilateral and 14% improvement in bilateral patients (both p < 0.05). Conclusions: In selected patients with early stage lymphoedema secondary to cancer treatment, LVA offers a minimally invasive surgical option that can achieve significant volumetric and quality of life improvements.